KEY DETERMINANTS OF LITHUANIA’S SOVEREIGN CREDIT RATING - Pačebutaitė, Aušra (Ekonomika, 2011)
The topic concerning the determinants affecting sovereign credit ratings of a country became extremely relevant after the recent economic turbulence which brought relentless downgrades, especially for Central and Eastern European (CEE) countries in their sovereign credit ratings. In the face of economic downturn around the world, causing the reduced availability of global capital flows and the appetite for risk, it becomes essential for the countries to secure the high market grade ratings in order to be able to issue foreign debt to ensure the solvency of the country’s finances and to pursue a sound economic growth. The aim of the study was to elucidate the key determinants of the Lithuanian sovereign rating during the financial turbulence of 2008 and to explain their importance and dynamics through external borrowing costs of the country.